2020
DOI: 10.1177/0145561320952506
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Continuing Semielective and Emergency Otolaryngological Procedures During the COVID-19 Pandemic

Abstract: Introduction: During the COVID-19 pandemic, worldwide over 600,000 human beings died due to the cause of the disease. In order to deescalate the transmission rate and to avoid crush loading the countries medical health systems social distancing, face masks, and lockdowns have been considered essential by the majority of governments. Whereas some countries have highly reduced or completely stopped otorhinolaryngological procedures, other countries have continued selected surgeries. The objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…There may also be a risk of metastasis. [ 21 - 25 ] The pandemic has led to a backlog in the cases. This will put undue pressure on the fast movement of the cases and may hamper the attention of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be a risk of metastasis. [ 21 - 25 ] The pandemic has led to a backlog in the cases. This will put undue pressure on the fast movement of the cases and may hamper the attention of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic period, nasolacrimal and nasal surgical procedures were not recommended due to proximity to the nasal mucosa in the ophthalmology and otolaryngology guidelines. 5 However, some otolaryngology clinics reported that emergency surgeries can be performed by taking all precautions 10 . In addition, semielective cases were also taken by taking the necessary precautions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also possible for nasal, real-time, reverse transcription-polymerase chain reaction (RT-PCR) tests taken before surgery to show false negativity 9 . However, it is recommended that all precautions be taken in patients requiring emergency surgery, even if the PCR tests are negative 10,11 . These measures include personal protective equipment, operating room conditions, and avoidance of high aerosol formation during surgery [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have compared the results of our study with other publications reporting on the surgical outcomes in HNC operated during the period of the pandemic in Table 4 [24][25][26][27][28]. Currently, we only have single institution experience reporting on retrospective data.…”
Section: Discussionmentioning
confidence: 99%